(untitled) (Alternautas, 2022)
This article draws on the literature of public health in Latin America and Brazil to examine the role of health in the indigenous’ pursuit of their acquired rights, and their attempts to shape the terms of, and decisions in official health assistance amid COVID-19 (Chalhoub, 1996; Cueto and Palmer, 2015; Sowell, 2015; Westphal et al., 2007; Hochman, 2011; Gibson, 2019). Through the analysis of newspaper articles, reports from indigenous organizations, legislative decisions, constitutional and health rights, this paper seeks to answer the following question: how do the strategies indigenous peoples have developed to pressure the Brazilian government into fulfilling its constitutional responsibilities during the COVID-19 pandemic demonstrate their exercise of active citizenship and contribution to the strengthening of democracy?.